KLEPTOCRACY OF BRIBERY IN PROMOTING POSITION IN INDONESIA THE PERSPECTIVE OF THE SOCIOLOGY OF LAW - Muhibin, Mochamad; Nasution, Eli Sanur; Bima, Ghandi (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2022)
Clean Government and Good Governance has realized yet in Indonesia. It is proven by selling and purchasing the positions in various places still exist. The process of rotation, transfer, and promotion of civil servant (ASN) that should have been given to the competent employees did not run as it should. The field investigation shows that the existence of power transaction that makes position as an object of commerce. This article aims to examine the kleptocracy of selling and purchasing the positions in Indonesia. The perspective used is the sociology of law. The research methodology implements a normative legal methodology through a qualitative approach and analysis of the fraud triangle theory, Gone theory, Ramirez Torres theory and Icebery Model theory. The result of the study concludes that bureaucrats are often not transparent, corrupt and tend to carry out transactional practices. For this reason, it is necessary to change the recruitment system and overall monitoring of civil servant (ASN) bureaucracy.